Angiography with the 256-multislice spiral computed tomography and its application in evaluating atherosclerotic plaque and cerebral ischemia. Issue 30 (July 2018) - Sun, Pei-Pei; Feng, Ping-Yong; Wang, Qiang; Shen, Shan-Shan
Abstract : Abstract: Ulceration of carotid arterial plaque is associated with cerebral events. Detection of ulcerated plaques will benefit patient from stroke and other ischemic events. The aim of this study was to evaluate morphology of atherosclerotic plaques in the carotid arteries and to assess its clinical impact in predicting cerebral events. A total of 386 patients were examined with 256-multislice spiral computed tomographic angiography (MSCTA). It was found that 356 of the 386 patients had cerebral ischemic symptoms. Specifically, 35 patients had amaurosis fugax (AmF), 178 had transient ischemic attack (TIA), and 143 had ischemic stroke. Abnormal images were found in 658 carotid arteries by MSCTA. Of the 658 abnormal images of carotid arteries, besides the 34 cases of carotid arterial occlusion, 624 cases were atherosclerotic plaques. Of the 624 plaques, 394 (63.2%) were smooth surface plaques, 161 (25.8%) were irregular surface plaques, and 69 (11.1%) were ulcerated plaques. Incidence of ulcerated plaque was higher in the ischemic stroke patients (13.1%) compared with that in the TIA group (10.3%), AmF group (6.6%), or symptom-free group (9.4%) although it was not statistically significant ( P  = .288). However, there was significant difference in the incidence of ischemic stroke between the ulcerated (20/69, 28.9%) and nonulcerated groups (69/555, 12.4%, P  < .05, odds ratio = 2.875). These findings suggested that 256-MSCTA is an advanced imaging tool to determine not only arterial stenosis but also morphologic assessment of atherosclerotic plaques, which will benefit the patients by predicting the cerebral events in advance.